Upaya Meningkatkan Disiplin Anak Melalui Permainan Ular Tangga Bercerita di Paud Arifah Kec. Medan Perjuangan Tahun Ajaran 2021-2022 - Juni Namawaddah Lubis; Darajat Rangkuti (Medan Resource Center, 2022)
This study aims to improve children's discipline through the game of snakes and ladders telling stories at PAUD Arifah Kec. Field of Struggle for Academic Year 2021-2022. This type of research is Classroom Action Research (CAR) which is carried out collaboratively with classroom teachers which is carried out in two cycles. Each cycle consists of planning, action, observation and reflection. The subjects in this study were children consisting of 12 children, 5 boys and 7 girls. Methods of data collection is done by observation, interviews and documentation. The data analysis technique used is descriptive quantitative and qualitative. Based on the results of the study, it was obtained that the average percentage of children's discipline during the pre-cycle was 36.80% which was included in the criteria for starting to develop and increased in the first cycle with an average percentage of 60.40% which was included in the criteria for developing as expected and in the second cycle. the average percentage showed an increase of 87.49% which was included in the very well developed criteria. Thus, it can be concluded that the discipline of children in PAUD Arifah Kec. The Struggle Field for the 2021-2022 Academic Year can be improved through the story-telling snake and ladder game.